Analysis of the Biological Quality of Clean Water in the Laju River, Dompu City - Mulhidin Mulhidin; Sri Wahyuningsih (Jurnal Pijar MIPA, 2026)
Water quality in Indonesia has been declining from year to year. One of the bodies of water experiencing declining water quality is the river. The decline in water quality, accompanied by bacterial contamination, contributes to various diseases linked to contaminated water. The Laju River is one of the large rivers located in the heart of Dompu City. The many activities of residents around the river are one of the sources of pollution in the Laju River. The purpose of this study is to determine the presence and number of Coliform bacteria and Escherichia coli. This type of research is Qualitative Descriptive research. Laju river water samples were taken from the upstream, middle and downstream sections. Based on the examination results, the highest number of Coliform bacteria was in the middle section of the river, namely 16,800 CFU/ 100 ml, and the highest number of Escherichia coli was in the upstream section of the river, namely 17,000 CFU/100 ml. The number of Coliform and Escherichia coli in Laju River water exceeds the value of the Class II River Water Quality Standards set by Government Regulation No. 22 of 2021. Reducing the levels of Coliform and Escherichia coli in river water requires a gradual approach, starting with physical treatment and progressing to chemical disinfection. Controlling the levels of Escherichia coli and Coliform in water is essential because these bacteria are the main indicators of dangerous pathogen contamination, serve as a standard for water quality suitability, and help detect sanitation damage.